Vulnerability of Philippine Amphibians to Climate Change. - Alcala, Angel C.
There are currently recognized 107 species of Philippine amphibians. In addition, several possible new species await formal taxonomic description. Most of them occupy microhabitats in moist or wet tropical rainforests. Based primarily on their known reproductive modes and microhabitats (including altitudinal distributions), the vulnerability of each amphibian species was assessed. The results of our assessment indicate that 26 species (24.30 percent) are highly vulnerable, 48 species (44.86 percent) are moderately vulnerable, 27 species (25.23 percent) are vulnerable, and 6 species (5.61 percent) are least vulnerable to climate change. However, this preliminary assessment is tentative and requires verification through field studies using other sets of indicators. Additionally, virtually all new species currently awaiting description are known from forested mountain habitats. These species are deemed disproportionately susceptible to climate change. Thus, the percentages of vulnerable tax are expected to climb sharply with ongoing taxonomic and ecological studies.
Keywords: Amphibians; Climate change; Montane; Moisture-dependent.; Philippines; Vulnerability